Factors Influencing the Usage of Twitter During Presidential Elections in Nigeria: Determinants of Usage of Twitter During Presidential Elections in Nigeria - Kolawole, Kayode David; Oyasor, Emmanuel (The Indonesian Journal of Computer Science, 2024)
This study examined the factors influencing the usage of Twitter during presidential elections in Nigeria. The population of the study comprises those under the age of voting in Nigeria that has Twitter account in Nigeria. Creswell (2012) sampling technique was used to select 576 respondents in Nigeria who have twitter account and are in voting age. Data was obtained through questionnaire administration. Structural Equation Modelling method of multiple regression analysis were used to achieve the objectives of the study. Results of the regression analysis revealed that factors (such as compatibility, cost effectiveness, interactivity, trust, ease of use and networking capability) are significant determinant of usage of Twitter during presidential elections in Nigeria at 1% and 5% level of significance. The study concluded that there are factors influencing the usage of twitter during presidential elections in Nigeria. Therefore, it is advised that politicians should always seek for information through social media that might improve their interactions with various populace. Therefore, social media adoption becomes essential due to its multifaceted and symmetrical nature.